Sosialisasi Tata Kelola Pencatatan Keuangan Bagi Pemilik Warung Di Lokasi Bumi Perkemahan Palutungan Desa Cisantana - Agustina, Ika; Asmanah, Yandi; Aisa, Neila; Hajar, Elvira Sitna; Amalia, Fisi (Jurnal Pengabdian Multidisiplin, 2024)
This activity aims to enhance the understanding and implementation of financial record management among stall owners at the Bumi Perkemahan Palutungan (Buper Palutungan) tourist site in Cisantana Village. Stall owners at Buper Palutungan play a strategic role in enhancing the attractiveness and welfare of tourists. However, a lack of understanding of financial record management can hinder business growth and effective financial management. The goal of this activity is to improve the understanding and skills of stall owners in financial record management, enabling them to manage their businesses more efficiently. The activity was conducted in March 2024 at Buper Palutungan with 25 stall owners participating. The method employed involved socialization through training and direct practice. The material was presented in a practical approach relevant to the needs of the stall businesses at the location. The results achieved have enhanced and increased a better understanding of financial recording among business operators. Positive implications are expected to improve the quality of their business financial management, which in turn can enhance competitiveness and contribute to the development of local tourism.